Respon Pertumbuhan Kelapa Sawit (Elaeis Guineensis Jacq.) Varietas Dyxp Dumpy pada Kondisi Stres Air di Pembibitan Awal - Wagino, Wagino; Tarigan, Sri Murti; Febrianto, Eka Bobby (Universitas Medan Area, 2018)
Global climate exchange especially rainfallspurs the growth of oil palm adapt to environmental conditions, so the development of oil palm plantations requires seeds that are able to adapt well in drought conditions.This study aims to determine whether water stress affects the growth of oil palm seedlings and sees the response of the level of resistance of oil palm seeds to drought stress.This research was carried out in the greenhouse garden experiment Medan STIPAP was conducted from January to June 2018. This study used Non-factorial Randomized Block Design (RBD), which consisted of 3 levels, 3 samples and 3 replications. Parameters to be observed were plant height, stem base diameter, leaf number, root wet weight, root dry weight, plant wet weight, plant dry weight, root volume, root length, stomatal density and number of stomata.The results showed that the difference in giving A1 water (100%) was significantly different from A2 (60%) and A3 (20%) on the parameters of oil palm seedling growth especially for the parameters of plant height, root wet weight, root dry weight, plant wet weight, plant dry weight, root volume, and root length while the base diameter of the stem, number of leaves, stomatal density and number of stomata give no significant effect. Drought stress effected to reduce the growth of stem diameter.